Influence of organizational internal change aspects on employee performance at selected retail sector Johor Bahru, Johor - Yong, Pei Zhen (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study aims to examine the influence of change aspects on employee performance in retail sector. The change aspects that will further discussed include communication, readiness for change, and transformational leadership. The research location that been selected was one of the mall retail sector located at the Johor Bahru while sample size included in this project was 43 respondents who hold executive and non-executive post in the retail sector. The simple random sampling technique was used as the questionnaire was equally distributed among the respondents. The Statistical Package for Social Science (SPSS) was version 22 was used to analyzed the data collected. The results showed that the 2 of independent variables which is readiness for change and transformational leadership has significant influence on employee performance in studied retail sector while communication doesn't show any significance correlation on employee performance. Furthermore, the studied also showed that the readiness for change was the most dominant independent variable that can determine the employee performance in studied retail sector. Lastly, implication and recommendation to the organization and HR practitioners have been further discussed.